The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/medicina58111675
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Phenotypic and Genotypic Characterisation of Carbapenem-Resistant Enterobacterales

Abstract: Improper use of antimicrobials has resulted in the emergence of antimicrobial resistance (AMR), including multi-drug resistance (MDR) among bacteria. Recently, a sudden increase in Carbapenem-resistant Enterobacterales (CRE) has been observed. This presents a substantial challenge in the treatment of CRE-infected individuals. Bacterial plasmids include the genes for carbapenem resistance, which can also spread to other bacteria to make them resistant. The incidence of CRE is rising significantly despite the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 109 publications
0
15
0
Order By: Relevance
“…Among the 53 CRE in our study, Klebsiella pneumoniae was the most predominant species, representing 69.8%, followed by E. coli (28.3%) and Klebsiella oxytoca (1.9%). Similarly, in Turkey, Baran and Aksu reported that the most common CRE species was Klebsiella pneumoniae (38.12 %), followed by E. coli (7.18 %) and Klebsiella oxytoca (0.55 %) 35 . On the contrary, a study in Nigeria reported that the most common CRE species were K. oxytoca 41%, then K. pneumoniae 32% and E. coli 27% 36 .…”
Section: Discussionmentioning
confidence: 84%
“…Among the 53 CRE in our study, Klebsiella pneumoniae was the most predominant species, representing 69.8%, followed by E. coli (28.3%) and Klebsiella oxytoca (1.9%). Similarly, in Turkey, Baran and Aksu reported that the most common CRE species was Klebsiella pneumoniae (38.12 %), followed by E. coli (7.18 %) and Klebsiella oxytoca (0.55 %) 35 . On the contrary, a study in Nigeria reported that the most common CRE species were K. oxytoca 41%, then K. pneumoniae 32% and E. coli 27% 36 .…”
Section: Discussionmentioning
confidence: 84%
“…This could be problematic when trying to detect chromosomal AMR genes. Nonetheless, the most prevalent BSI causative antimicrobial resistance strains (MRSA, Vancomycin-Resistant Enterococcus , Multidrug-Resistant Enterobacteriaceae , Extended-Spectrum β-Lactamase (ESBL) gram-negative species or Carbapenem-Resistant Enterobacterales [ 56 ]), generally have plasmid-mediated resistant mechanisms [ 71 75 ]. Because of the low coverage obtained in two of the genes present on the plasmid ( aac6’-lb-cr and catB4 ), these were misidentified as closely related genes: aac(6’)-lb-W104R, aac(6’)-lb-D181Y, aac(6’)-lb-AKT and catB3 .…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenem-resistant Enterobacterales (CRE) are a major concern in the community and in healthcare settings [ 1 ]. Among the carbapenamases, NDM, with the exception of aztreonam, mediates resistance to all β-lactam antibiotics [ 2 ].…”
Section: Introductionmentioning
confidence: 99%